A Missed Opportunity: Extragenital Screening for Gonorrhea and Chlamydia Sexually Transmitted Infections in People With HIV in a Southeastern Ryan White HIV/AIDS Program Clinic Setting. (1st July 2022) - Geba, Maria C; Powers, Samuel; Williams, Brooke; Dort, Kathryn R; Rogawski McQuade, Elizabeth T; McManus, Kathleen A
Abstract: Background: Guidelines recommend annual screening for gonorrhea/chlamydia in sexually active people with HIV at multiple sites (urogenital, oropharyngeal, rectal). In the first year of multisite screening at our Ryan White HIV/AIDS Program clinic, we studied (1) sexual history documentation rate, (2) sexually transmitted infection (STI) screening rate, (3) characteristics associated with STIs, and (4) the percentage of extragenital STIs that would have been missed without multisite screening. Methods: Participants were ≥14 years old with ≥1 in-person medical visit at our clinic in 2019. Descriptive analyses were performed, and adjusting for number of sites tested, a log-binomial model was used to estimate the association between characteristics and STI diagnosis in men. Results: In this cohort (n = 857), 21% had no sexual history recorded. Almost all STI diagnoses were among males (99.3%). Sixty-eight percent (253/375) received appropriate urogenital testing, 63% (85/134) received appropriate oropharyngeal testing, and 69% (72/105) received appropriate rectal testing. In male participants with ≥1 STI test (n = 347), Hispanic ethnicity and having a detectable HIV viral load were associated with an STI diagnosis. Of those diagnosed with an STI who had multisite testing, 96% (n = 25/26) were positive only at an extragenital site. Conclusions: Screening rates were similar across all anatomical sites, indicating no obvious bias against extragenital testing. In males, STIs were more frequently diagnosed in people who identify as Hispanic and those with detectable viral loads, which may indicate more condomless sex in these populations. Based on infections detected exclusively at extragenital sites, our clinic likely underdiagnosed STIs before implementation of multisite screening.